Urgensi Sui Generis Regime Permintaan Slot Geostationary Orbit melalui Perspektif Negara Khatulistiwa Khususnya Indonesia - Andriwinata, Rackel; Palguna, I Dewa Gede (Jurnal Penelitian Hukum De Jure, 2024)
Indonesia is one of the countries whose position is crossed by the equator, which is parallel to the Geostationary Orbit (GSO). The passing of Law No. 16 of 2002 marks Indonesia’s binding to the Outer Space Treaty, which encourages Indonesia to have regulations regarding the resolution of issues relating to the use of GSO slots in the national interest. Indonesia proposes a special legal regime that recognizes GSO as an independent territorywithout disturbing existing rules. This research emphasizes the urgency of creating a fair and equitable legal framework in utilizing GSO, especially for developing countries. This research aims to explore legal certainty in the context of space utilization and exploration, especially Geostationary Orbit (GSO). This research uses a normative juridical method with the main approaches, namely legislation and conceptual. The results show the needfor a special regime that regulates the utilization of GSO so that there is no gap between countries with the principles of maintaining peace, justice and mutual benefit, with the hope of providing clarity of rules and guidelines in exploring and utilizing space safely and fairly.